Nemu Gelang Wewengkon Desa lan Karang Paumahan of Bayung Gede as an Ecology-Based Local Wisdom - Mitha Mahastuti; Arya Wijaatmaja (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Bali has unique methods to preserve environment sustainability, for example: folklore, legend, tale, custom and concept that contain prohibition to do particular activities that could damage the environment. One of the ancient villages (Bali Aga) that has ecology friendly concept is Bayung Gede. This article tries to find how an ecology-based local wisdom evocation can sustain the environment in a growing rural area, especially in Bayung Gede. This article uses a qualitative method through observation and interview. Nemu Gelang refers to the layered green open space arrangement, which has architecture-profane and sacred functionality, on almost entire direction forms a series of layered “green barrier” which is called Nemu Gelang. The existence of these layered open spaces, in the traditional settlements known as